Diversity of Management Practices of Human Resources and their Impact on Entrepreneurship in Universities: A Field Study in Public Jordanian Universities - الليمون عودة عطية; الربابعة فاطمة علي (Journal of Economics and Administrative Sciences, 2019)
The purpose of this study is to examine the effect of human resource diversity management practices on achieving entrepreneurship in Jordanian public universities. To achieve the aims of the study, a well-designed questionnaire was used for collecting data. The population of the study was (7433) faculty members (including different ranks such as professors, associate professors, assistant professors and lecturers) in Jordanian public universities. The study sample was selected through the use of a random sample, the questionnaire is distributed to a sample (of 400 with the percentage of 5%) selected by using a random sampling (350) copies of the questionnaire were collected, reaching about (87.5%) out of the sum total of the distributed copies. Descriptive and inferential statistics were used in data analysis. The study uncovers some significant results. First, the participants’ perceptions of the practices of managing the diversity of human resources in different dimensions were medium and the perceptions of the participants towards achieving entrepreneurship in different dimensions were similarly medium. Second, there is a statistically significant difference in the practices of human resource diversity along with all dimensions in achieving entrepreneurship along with all dimensions in public universities. The study recommends the paramount importance of activating the role of university in effectively benefiting from the diversity of positive human resources as a management method in executing tasks. The study emphasis on offering and institutionalizing training courses which enhance entrepreneurship skills and the capacities of faculty members.